Diffusion and mass transfer - Vrentas, James S.; Vrentas, Christine Mary Jarzebski, 1953- (CRC Press, 2016)
A proper understanding of diffusion and mass transfer theory is critical for obtaining correct solutions to many transport problems. Diffusion and Mass Transfer presents a comprehensive summary of the theoretical aspects of diffusion and mass transfer and applies that theory to obtain detailed solutions for a large number of important problems. Par